2019
DOI: 10.1021/acs.macromol.8b02529
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplexes of Discrete, Isotactic Lactic Acid Oligomers Conjugated with Oligodimethylsiloxanes

Abstract: Discrete length block co-oligomers (BCOs) comprised of a crystalline and an amorphous block are a new class of materials that gives highly ordered lamellar morphologies at small length scales. Here, we show the preparation of discrete, isotactic oligo l- and d-lactic acid (olLA and odLA) homoblocks followed by ligation to oligodimethylsiloxane (oDMS), affording a library of crystalline–amorphous BCOs that vary in molecular weight and composition. Mixing the two enantiomeric BCOs or homoblocks results in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…1e and Table S1 †), indicating that all these crystals adopt an extended chain conformation (Scheme 1b). 36 Extrapolating the linear t to x ¼ 0 gives the thickness of the amorphous layer (d a ¼ 0.91 nm, mainly the protecting group, assuming 100% crystallinity), and the thickness of the crystalline layer (d c ) can thus be calculated accordingly…”
Section: Crystallization Behaviors Of Discrete Ollasmentioning
confidence: 99%
See 2 more Smart Citations
“…1e and Table S1 †), indicating that all these crystals adopt an extended chain conformation (Scheme 1b). 36 Extrapolating the linear t to x ¼ 0 gives the thickness of the amorphous layer (d a ¼ 0.91 nm, mainly the protecting group, assuming 100% crystallinity), and the thickness of the crystalline layer (d c ) can thus be calculated accordingly…”
Section: Crystallization Behaviors Of Discrete Ollasmentioning
confidence: 99%
“…The slope of the linear t, on the other hand, indicates an increase of 0.307 AE 0.003 nm per monomeric residue, which is in good agreement with the crystal unit cell parameters. 36 For polymer lamellar crystals, the relationship between T m and d c can be described by the Thomson-Gibbs equation (eqn (1))…”
Section: Crystallization Behaviors Of Discrete Ollasmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Most recently, Meijer reported that four lactic acid repeat units were needed to obtain SC crystallites. 16 It seems that the minimum block length of PDLA to form SC crystallites may change because of the chemical structure of PDLA. As a result, it is also necessary to identify if the minimum block length of PDLA to form SC crystallites would change in copolymers with outer PDLA blocks to from SC crystallites with a PLLA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Hennink reported that a minimum degree of polymerization (DP) of lactic acid oligomer was required to form SC crystallites, and crystallization occurred at DP ≥ 7 in a blend of d ‐ and l ‐lactic acid oligomers 15 . Most recently, Meijer reported that four lactic acid repeat units were needed to obtain SC crystallites 16 . It seems that the minimum block length of PDLA to form SC crystallites may change because of the chemical structure of PDLA.…”
Section: Introductionmentioning
confidence: 99%